2007
DOI: 10.1002/dc.20621
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound‐guided biopsies of pancreatic masses: Comparison between fine needle aspirations and needle core biopsies

Abstract: Endoscopic ultrasound-guided fine needle aspiration (EUS-guided FNA) is a highly sensitive and specific method for diagnosing pancreatic masses. Alternatively, EUS-guided needle core biopsies (NCB) have also been introduced. We sought to determine efficacies of pancreatic EUS-guided FNAs and NCBs. Records of consecutive EUS-guided FNAs received over a 24-mo-period were reviewed. Cases with concurrent NCBs were selected for the study. The diagnoses from the two modalities were compared and designated concordant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 25 publications
(57 reference statements)
0
14
0
1
Order By: Relevance
“…For CS, the relatively high unsatisfactory sample rate as compared to the corresponding rates in previous studies was probably due to the omission of on‐site cytology assessment; the cellularity and adequacy of specimens should be checked by a pathologist at the time of the procedure. On‐site assessment for adequacy of the FNA specimen has been emphasized in previous studies 21,22 . Moreover, we suggest that the split sample protocol brought about the high rate of unsatisfactory specimens for the LBC method.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…For CS, the relatively high unsatisfactory sample rate as compared to the corresponding rates in previous studies was probably due to the omission of on‐site cytology assessment; the cellularity and adequacy of specimens should be checked by a pathologist at the time of the procedure. On‐site assessment for adequacy of the FNA specimen has been emphasized in previous studies 21,22 . Moreover, we suggest that the split sample protocol brought about the high rate of unsatisfactory specimens for the LBC method.…”
Section: Discussionmentioning
confidence: 62%
“…In many studies, the false‐negative diagnosis of EUS‐FNA might be secondary to sampling and the nature of the neoplasm and rather than interpretation. Micrometastasis, intrinsic shortcomings of the biopsy apparatus, the location and size of the lesion, gauge of the needle, resolution of the probe, and the ability to visualize and guide the needle may have also contributed to false‐negative results 12,21,23 . No case of false‐negative result was caused by an interpretation error in our study.…”
Section: Discussionmentioning
confidence: 63%
“…When performed transgastrically, the technique appears to be safe 96 . Recently, some authors have reported higher sensitivity for diagnosing pancreatic neoplasms for EUS-guided FNA compared with EUS-guided core biopsy 58,80,82 , but others have not 81 . The adequacy of sampling and diagnostic accuracy may be enhanced by combined EUS-guided FNA and EUS-guided trucut needle biopsy 58,81 .…”
Section: Endoscopic Ultrasound-guided Trucut Needle Biopsymentioning
confidence: 98%
“…A further seven studies on percutaneous 76 -79 or EUS-guided core biopsies 80 -82 of pancreatic masses met the inclusion criteria. Two studies evaluated EUS-guided FNA in combination with EUS-guided core biopsy 58,80 .…”
Section: Data Extractionmentioning
confidence: 99%
“…1 Therefore, rapid and accurate assessment of a pancreatic mass is important to direct patient management. 2 …”
mentioning
confidence: 99%